The role of thoracoscopic pneumonectomy in surgical treatment of lung diseases - V. A. Porkhanov; V. V. Danilov; V. B. Kononenko; N. V. Naryzhnyi; A. L. Kovalenko; V. V. Shtraub; V. A. Zhikharev (Вестник хирургии имени И.И. Грекова, 2019)
The objective was to estimate the immediate results of thoracoscopic pneumonectomies in various surgical lung diseases.Material and methods. Patients were divided into groups depending on the surgical access: thoracoscopy – group 1 (15 patients), thoracotomy – group 2 (30 patients). We performed 12 left-sided (80 %) and 3 right-sided (20 %) operations in group 1. We performed 23 left-sided (76.7 %) and 7 right-sided (23.3 %) operations in group 2.Results. The average duration of the operation in group 1 was (161±27) min (from 120 to 230 min), in group 2 – (128±34) min (from 75 to 180 min). The number of removed lymph nodes during lymphadenectomy in group 1 was (19±10) nodes (from 6 to 40), in group 2 – (18±9) nodes (from 6 to 38). The severity of the pain syndrome after surgery on the Visual Analogue Scale for Pain in group 1 was 2.4±0.3, in group 2 – (4.4±0.3) (p=0.04), duration of ICU stay in group 1 was (2.0±0.7) days (from 1.0 to 3.0), in group 2 – (4.1±1.2) days (3.0 to 6.0). There were no mortality in both groups.Conclusion. In carefully selected patients, thoracoscopy access during pneumonectomy demonstrates better immediate results comparing to thoracotomy (less pain syndrome, shorter duration of treatment in the ICU, hospital) with the same duration of operation and volume of lymph dissection.